Excess weight and cardiometabolic risk among faculty members at a private university of Lima: Opportunity to build healthy environments - Morales, Juan (2018)
Introduction: Global mortality due to noncommunicable diseases is high and increasing. In Peru it represents 66% of the deaths. Objective: The objectives of this study were to determine the frequency of obesity and overweight, and to evaluate cardiovascular and metabolic risk. Materials and methods: A cross-sectional descriptive study developed between July and November of 2016, the participants were faculty members of a private university located in the northern area of Lima. To determine the overweight and obesity was used the body mass index; cardiovascular and metabolic risks were assessed with the abdominal perimeter; and the risk of diabetes mellitus was determined using the FINDRISC questionnaire. Results: Of the 164 participating teachers, 51.8% (n = 85) were less than 45 years old, 73.2% (n = 120) were males, 3% (n = 5) had a history of hypertension and 5.5% (n = 9) diabetes mellitus, 47.6% (n = 78) were overweight and 31.1% (n = 51) were obese. Excluding the history of arterial hypertension and diabetes mellitus, the level of cardiovascular risk was high in 32.7% (n = 49), very high in 42% (n = 63), with significant differences between genders (P =.001). Regarding the risk of developing diabetes mellitus, in 36.7% (n = 55) it was slightly elevated, 12.7% (n = 19) moderate, 5.3% (n = 8) high, 0.7% (n = 1) very high, without significant differences between genders (P =.568). Conclusions: Among faculty members there are a high frequency of overweight and obesity, and present high cardiovascular and metabolic risk. It is necessary to strengthen the promotion of healthy lifestyles mainly in the consumption of healthy foods and the increase of the physical activity.